1996
DOI: 10.1080/00288233.1996.9513166
|View full text |Cite
|
Sign up to set email alerts
|

Single trait selection for yearling fleece weight or liveweight in Romney sheep—correlated responses in liveweight, fleece traits, and ewe reproduction

Abstract: An experiment was carried out to study direct and indirect responses to selection in Romney sheep. There were two selection lines, one selected for greasy fleece weight (GFW) and the other for liveweight (LW), maintained alongside a control line (CO). Data from lambs born in 1967-90 were analysed to quantify the correlated responses to selection. By 1990, there had been an average of nine generations of selection with an average generation interval of 2.7 years. The correlated responses analysed included yearl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

1999
1999
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 9 publications
0
7
2
Order By: Relevance
“…In another experiment at Whatawhata and Tokanui, treating the survival data as a trait of the ewe instead of the lamb, we found that the h 2 for lamb survival was also very low (0.02), and the repeatability was 0.07 (Morris et al 1996). In conclusion, genetic parameters for perinatal and preweaning survival were small under all conditions evaluated, and within-breed opportunities for genetic improvement of survival appear quite limited.…”
Section: Random Effectsmentioning
confidence: 85%
See 2 more Smart Citations
“…In another experiment at Whatawhata and Tokanui, treating the survival data as a trait of the ewe instead of the lamb, we found that the h 2 for lamb survival was also very low (0.02), and the repeatability was 0.07 (Morris et al 1996). In conclusion, genetic parameters for perinatal and preweaning survival were small under all conditions evaluated, and within-breed opportunities for genetic improvement of survival appear quite limited.…”
Section: Random Effectsmentioning
confidence: 85%
“…However, corresponding calf:dam weight data in cattle (Morris et al 1986) were associated with differences in perinatal survival. Selection for yearling liveweight in sheep leads to correlated changes in dam weight (e.g., pre-mating weight) and in BW (Morris et al 1996). Further analyses would be required to test whether different BW optima in Romneys might be associated with genetically different ewe weights.…”
Section: Fixed Effectsmentioning
confidence: 99%
See 1 more Smart Citation
“…After mating, ewes were separated from rams and kept as one group until the lambing season which usually starts in August to October. (Morris et al 1996;Morris et al 2000;Ibrahim 2015, respectively).…”
Section: Animal Datamentioning
confidence: 99%
“…It is unclear, however, whether a higher fleece weight is associated with an increase in other fleece characteristics (length, diameter, compression and secondary to primary follicle ratio) of Angora rabbits. In sheep, Morris et al (1996) found an unfavourable Available online at www.sciencedirect.com Livestock Science 113 (2008) 8 -13 www.elsevier.com/locate/livsci correlated response in mean fibre diameter when selecting for high fleece weight. In a companion paper, Rafat et al (2007) presented results of a divergent selection experiment on total fleece weight in French Angora rabbits.…”
Section: Introductionmentioning
confidence: 98%